2002
DOI: 10.1063/1.1501757
|View full text |Cite
|
Sign up to set email alerts
|

Frequency upconversion involving triads and quartets of ions in a Pr3+/Nd3+ codoped fluoroindate glass

Abstract: Frequency upconversion ͑UC͒ processes involving energy transfer ͑ET͒ among Nd 3ϩ and Pr 3ϩ ions in a fluoroindate glass are reported. In a first experiment, the excitation of Pr 3ϩ ͓transition 3 H 4 → 1 D 2 ͔ and of Nd 3ϩ ͓transition 4 I 9/2 →( 2 G 7/2 ϩ 4 G 5/2 )͔ was achieved with a dye laser operating in the 575-590 nm range. In a second experiment, the Nd 3ϩ ions were excited with the second harmonic of a Nd: YAG laser at 532 nm. The ET processes leading to UC in both experiments were studied by monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…4 Various UC processes that involve different RE ions have been demonstrated and indicate that FIG is a promising host material for UC based devices. [5][6][7][8][9][10] Besides choosing a good host material for RE ions, the efficiency for infrared-to-visible and ultraviolet light conversion can be improved if one uses a sensitizer to increase near-infrared absorption. In this case, the ytterbium (Yb 3ϩ ) ion has been used because it contains only one electronic transition inside the 4f subshell, which guarantees a large ground-state absorption cross section.…”
Section: Introductionmentioning
confidence: 99%
“…4 Various UC processes that involve different RE ions have been demonstrated and indicate that FIG is a promising host material for UC based devices. [5][6][7][8][9][10] Besides choosing a good host material for RE ions, the efficiency for infrared-to-visible and ultraviolet light conversion can be improved if one uses a sensitizer to increase near-infrared absorption. In this case, the ytterbium (Yb 3ϩ ) ion has been used because it contains only one electronic transition inside the 4f subshell, which guarantees a large ground-state absorption cross section.…”
Section: Introductionmentioning
confidence: 99%
“…This is clearer when energy levels closer to the surface plasmon resonance participate in the UC process. Finally, the present results suggest that the presence of silver nanoparticles may enhance UC processes of high order, such as the ones involving triads and quartets of Pr 3+ , 19,20 by a factor much larger than is shown here for ion pairs. …”
Section: Resultsmentioning
confidence: 68%
“…22͒ and Pr 3+ /Nd 3+ . 23 A process involving ET among three excited Er 3+ ions was used to construct a practical temperature sensor. 24 The studies of UC due to ET in fluoroindate glasses have demonstrated the large potential of these materials for devices because of their large transparency window, the low multiphonon emission rates, and the high fluorescence efficiency of RE ions hosted in these glasses.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In fluoride glasses, many ET processes were observed and successfully exploited. [3][4][5][16][17][18][19][20][21][22][23] For example, the efficient ET process in Nd 3+ -Pr 3+ pairs was exploited to obtain blue laser emission in fluorozirconate glass. 16 In fluoroindate glasses, besides the observation of ET involving RE pairs, [17][18][19][20] ET processes involving triads and quartets of ions were investigated in samples doped with Er 3+ ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation